A bomba estourou: fraseologismos de São Luís do Maranhão nos discursos semidirigidos do projeto Alib - PEREIRA, Karla Karoline de Fátima Silva (2019)
Phraseology is the branch of Lexicology that deals with the construction of expressions or phrases, proper to a language, usually with figurative sense, such as bater peso, fazer na doida, longe pra caramba, ficar meio assim. There are many classifications when it comes to phraseological units and it is not always possible to reach a consensus between them. However, some characteristics inherent to these units were observed and tested in the phraseologisms selected for this research, such as polylexicality, fixity, opacity, congruence and variation. This study adopts concepts from the french phraseology, following mainly the postulates of Salah Mejri (1997, 2012, 2017, 2018), Gaston Gross, Inês Sfar (2016, 2018) and Marcela Paim (2016, 2018, 2019) , and its main objective is to make a survey of phraseologisms in São Luís do Maranhão, using data obtained from Temas para Discursos Semidirigidos (TDS) of the Projeto ALiB - Atlas Linguístico do Brazil. To carry out this study, we adopted the following steps: a) selection of phraseologisms found in the narratives obtained through the questionnaires applied in the surveys conducted by the Projeto ALiB; b) structural and semantic analysis of the selected expressions; and c) verification of the registration of such expressions in general dictionaries of the Portuguese language and dictionaries specialized in phraseology. The research subjects were divided into two age groups, described as follows: Age range I - 18 to 30 years; Age range II - 50 to 65 years. There are eight informants of both sexes (male and female) and have elementary and higher education. The aspects analyzed and tested in this research were of fundamental importance so that we could reach the final product for which this work is intended: the construction of a glossary that will support the Projeto Valextra (Variação Lexical: teorias, recursos e aplicações): do condicionamento lexical às constrições pragmáticas, the purpose of which is the elaboration of a bilingual (Portuguese / French) dictionary of phraseologisms.